The Journals of Economics - Stigler, George J.; Stigler, Stephen M.; Friedland, Claire (Journal of Political Economy, 1995)
We examine the principal journals of economics, with particular attention to the communication between journals, as reflected by the network of interjournal citations during 1987-90, and the changes over the past century in the characteristics of the authors and the techniques they have used. The numerical results, and those of the statistical modeling of these results, reinforce the importance of economic theory as an exporter of intellectual influence to applied economics. The study includes an examination of the degree of specialization among different subfields of economics. A statistical model is presented for measuring the flow of intellectual influence (as measured by citations) in terms of simple univariate scores.